Pengaruh Pemasaran Digital terhadap Penjualan Es Teh Djanoko Bayat pada Usaha Kecil Menengah (UKM) : Studi Kasus pada SDN DAON 3 - Tri Windarsih; Muzakar Isa (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2026)
This study aims to comprehensively examine the influence of digital marketing strategies, investment in digital technology, and customer engagement on the business performance of Micro, Small, and Medium Enterprises (MSMEs) with digital transformation as a mediating variable. A case study was conducted on the MSME Es Teh Djanoko Bayat. This research employs a quantitative methodology with a causal design. Data were collected through questionnaires distributed to 350 respondents and analyzed using the SmartPLS version 3 tool. The results indicate that digital marketing strategies and digital technology investment have a positive and significant effect on both digital transformation and performance improvement. Furthermore, digital transformation is proven to have a positive effect on performance. However, while digital customer engagement positively affects performance, it was found to have no significant effect on digital transformation. In conclusion, the effectiveness of digital marketing and technology investment are key drivers in the transformation process and company performance, while customer interaction impacts sales directly without triggering significant operational changes.